KANDUNGAN KARBOHIDRAT DAN SERAT PADA DAUN SEMBUKAN (Paederia foetida) - Astija Astija (Universitas Cokroaminoto Palopo, 2022)
Fart leaf plants (Paederia foetida) or Sembukan contain Alkaloids, flavonoids and Iridoid glycosides. The plants have various functions that are as antihepatotoxic, hypoglycemic, antispasmodic, anti-inflammatory, antitumor, antiviral, antidiarrheal, immunomodulatory, anti-rheumatic, anti-inflammatory. pain and seizure relief. Besides being used as herbal medicine, medicinal plants can also be used as complementary food ingredients because they are thought to contain nutrients such as carbohydrates and fiber. This study aims to determine the content of carbohydrates and fiber in sembukan. The carbohydrate content of sembukan leaves was analyzed using a UV-Vis spectrophotometer. The results showed that sembukan leaves contain carbohydrates including glucose 0.986 mg, fructose 0.99 mg, sucrose 1.710 mg, starch and fiber 7,03 grams per 100 grams of sembukan leaves